2022
DOI: 10.3389/fgene.2022.942153
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics Analysis Identifies Robust Biomarkers and Its Correlation With Immune Microenvironment in Nonalcoholic Fatty Liver Disease

Abstract: Objective: Nonalcoholic fatty liver disease (NAFLD) is a serious threat to human health worldwide. In this study, the aim is to analyze diagnosis biomarkers in NAFLD and its relationship with the immune microenvironment based on bioinformatics analysis.Methods: We downloaded microarray datasets (GSE48452 and GSE63067) from the Gene Expression Omnibus (GEO) database for screening differentially expressed genes (DEGs). The hub genes were screened by a series of machine learning analyses, such as support vector m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
2
2
0
Order By: Relevance
“…is nding -consistent with previous studies (Wen et al 2021;Zhang et al 2022) -suggests that immunity plays an essential role in NAFLD. Furthermore, based on 48 ERSR-DEGs, we identi ed two ERS-related clusters using unsupervised cluster analysis.…”
Section: Discussionsupporting
confidence: 92%
“…is nding -consistent with previous studies (Wen et al 2021;Zhang et al 2022) -suggests that immunity plays an essential role in NAFLD. Furthermore, based on 48 ERSR-DEGs, we identi ed two ERS-related clusters using unsupervised cluster analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Higher levels of M1 macrophage, M2 macrophage, resting dendritic cell, and resting mast cell infiltration were seen in patients with NAFLD, while lower levels of monocyte, activated dendritic cell, activated mast cell, eosinophil, and neutrophil infiltration were seen in these patients. These findings were consistent with previous studies that examined liver tissues (Wen et al, 2021;Zhang et al, 2022). In addition, we used unsupervised clustering analysis to illustrate the expression landscape of different disulfidptosis regulatory patterns underlying NAFLD patients based on DE-DRGs.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is necessary to move from the gene level to the pathway level, which can help to capture the heterogeneous patterns of tumors. Some studies have found patterns of mutations at the pathway level [ 3 , 4 ]. Most of these studies are based on known information about signaling pathways, and attempt to search pathway databases for pathways that drive cancer development.…”
Section: Introductionmentioning
confidence: 99%